Strategi Penanganan Resiko Terjadinya Kecelakaan Kerja Dengan Metode HFACS, HIRARC, dan Fuzzy Logic - Haqqi, Renda Sukma Saubil; Satya, Ririn Regiana Dwi Satya; Usman, Ridwan (Program Studi Teknik Industri, Fakultas Teknik, Universitas Bhayangkara Jakarta Raya, 2023)
Occupational Health and Safety (OHS) is an absolute necessity for humans when working. The purpose of this study is to determine the identification of negligence at work that results in errors and causes accidents and determine prevention strategies. The HFACS method is an accident analysis tool used to analyze an accident on the Human Factor aspect. Then continue with limiting the event of mishaps with the HIRARC technique which comprises of Peril Distinguishing proof, Chance Evaluation, and Hazard Control. HIRARC's point is that the perils that exist in each activity can be recognized and controlled rapidly so the potential for work mishaps can be restricted, then endeavors are made to order wellbeing utilizing the fluffy rationale technique. In view of the consequences of consolidating the HFACS and HIRARC strategies utilizing the Fuzzy, it tends to be presumed that the three techniques get a gamble rating worth of 6.33 which is remembered for the Moderate boundary class.